URGENSI AYAT AYAT AS SYIFA’ DALAM PENGOBATAN MODERN - Muthmainnah; Nur Wahyuni Emia Barus, Harun Al Rasyid (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
This research aims to explore the urgency of I'jaz al-Qur'an contained in the verse as syifa' which is often used as a form of modern treatment that is increasingly familiar everywhere. Even though this type of treatment has actually been around since the time of the Prophet Muhammad SAW, now many people are doing it. In this context, this research aims to understand the context of the verse as syifa which is often used in modern medicine The type of research used is Library Research, using primary data sources books and secondary data sources in the form of books, journals and other related articles. Then analyze it with content analysis techniques using reduction, presentation and conclusion methods. Analysis results shows that the understanding of I'jaz al-Qur'an regarding the verses as syifa' can not only be understood from the perspective of verses from the Qur'an, but also as healing. This research contributes to a deeper understanding of phenomena and events that the verses of the Qur'an can be healing and provides examples that have occurred. The implications of this research are expected to strengthen understanding of the Al-Qur'an as a book that not only has linguistic, literary, historical and social dimensions that are important to study and understood holistically but is really needed by our spirit in physical and material terms to become a healer.